Centro de desarrollo infantil - Poma Feijoo, Katherine Fernanda (2016)
Weather conditions The Coca has peculiar characteristics, which give a strong identity, as the presence of rainfall in most of the year, the rivers and jungle, however, throughout its history, the city has undergone physical changes in the natural territory, thanks to uncontrolled urbanization and the mistaken intervention of man, forgetting his environment and climate. Due to the uncontrolled growth of the city, it is clearly seen a cluster of facilities and basic services south of the city, leaving gradually supply up to the north of the city. After making the urban study and subsequently a proposal, it concludes revitalize and rehabilitates the city with a series of both urban and architectural equipment, the same as necessities respond to the sector. This degree work is a response to the current need of the sector from an approach to planning and urban design, low geographical, environmental and urban principles. The goal of the project, through all the analyzes and diagnoses, concepts, parameters and strategies, is to make a proposal, where a Child Development Center is raised, with an intervention methodology in terms of teaching methods and their urban environment.